2013
DOI: 10.1002/anie.201302158
|View full text |Cite
|
Sign up to set email alerts
|

Cooperative Catalysis in Glycosidation Reactions with O‐Glycosyl Trichloroacetimidates as Glycosyl Donors

Abstract: Thiourea mediates cooperative glycosidation through hydrogen bonding. N,N'-Diarylthiourea as cocatalyst enforces an SN2-type acid-catalyzed glycosidation even at room temperature (see scheme; Bn=benzyl). From O-(α-glycosyl) trichloroacetimidates as glycosyl donors and various acceptors, β-glycosides are preferentially or exclusively obtained.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
92
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 130 publications
(94 citation statements)
references
References 39 publications
1
92
0
1
Order By: Relevance
“…90 The same thiourea has also been employed as a catalyst for the selective addition of alcohols to glycals resulting in the formation of 2-deoxy-α-glycosides, although in this instance it is considered to function merely as a mild protic acid. 91–92 In related work chiral binol-derived phosphoric acid catalysts have been employed to promote cyclization of 1-(γ-hydroxypropyl)glycals and their homologs to spiroketals.…”
Section: Counterion and Additive Effectsmentioning
confidence: 99%
“…90 The same thiourea has also been employed as a catalyst for the selective addition of alcohols to glycals resulting in the formation of 2-deoxy-α-glycosides, although in this instance it is considered to function merely as a mild protic acid. 91–92 In related work chiral binol-derived phosphoric acid catalysts have been employed to promote cyclization of 1-(γ-hydroxypropyl)glycals and their homologs to spiroketals.…”
Section: Counterion and Additive Effectsmentioning
confidence: 99%
“…Despite the broad application of cooperative catalysis, it is still uncommonly employed in the area of carbohydrate chemistry, especially for glycosylation reactions, due to the prerequisite of having both catalysts being compatible under the reaction conditions. The Schmidt group has successfully applied the synergistic catalysts (thiourea derivatives with phosphorus acids) for stereoselective O -glycoside bond formation [30]. Similarly, Galan et al reported a method for the preparation of 2-deoxyglycosides from glycals under the influence of cooperative catalysis (chiral phosphoric acids/thiourea derivatives) [31].…”
Section: Introductionmentioning
confidence: 99%
“…24 Although the original study reported 6-dEB production titers as high as 129 mg/L in shake flask fermentation experiments, we were unable to reproduce these yields under the same conditions, typically acquiring ~5 mg/L of isolated material. Furthermore, quantification of 6-dEB production by LC-MS prior to culture extraction revealed that the low isolated yields were not due to loss of material from downstream workup, isolation, and purification procedures.…”
Section: Resultsmentioning
confidence: 87%